Kemampuan Berpikir Logis dan Penguasaan Kosa kata Bahasa Jerman - Hesti Lestari; Misnawaty Usman; Hasmawati Hasmawati (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2019)
There are many factors that can influence students' vocabulary mastery in foreign language learning. This study aims to determine the relationship between logical thinking skills and students' mastery of German vocabulary. Research is an experimental study involving only the experimental class without the control class. Data collection techniques are done through writing test and logical thinking test in the form of Intelligent Structure Test (IST). The sample in this study were 21 high school students selected through random sampling techniques. The results of the analysis of this study indicate that there is a significant relationship between the ability to think logically with students' mastery of German vocabulary. Students who have good critical thinking skills, tend to more easily remember and understand new vocabulary in learning foreign languages.